1988
DOI: 10.2307/2000924
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Model of the Complement of an Arrangement of Hyperplanes

Abstract: ABSTRACT. In this paper the methods of rational homotopy theory are applied to a family of examples from singularity theory. Let A be a finite collection of hyperplanes in C', and let M = C' -UHeA H. We say A is a rational K(ir, 1) arrangement if the rational completion of M is aspherical. For these arrangements an identity (the LCS formula) is established relating the lower central series of tt\ (M) to the cohomology of M. This identity was established by group-theoretic means for the class of fiber-type arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Concerning the cohomology algebra of M (A), Orlik and Solomon [OS80] showed that it is determined by L(A) by constructing a combinatorial algebra which is isomorphic to H • (M (A)), previously computed by Arnol'd and Brieskorn [Bri73] in some outstanding cases. Using Sullivan 1-minimal models, Falk proves that also φ k (G A ) is combinatorially determined [Fal88]. He also obtains with Randell [FR85], in the particular case of fibertype arrangements, the LCS formula:…”
Section: Lower Central Series Quotientsmentioning
confidence: 89%
“…Concerning the cohomology algebra of M (A), Orlik and Solomon [OS80] showed that it is determined by L(A) by constructing a combinatorial algebra which is isomorphic to H • (M (A)), previously computed by Arnol'd and Brieskorn [Bri73] in some outstanding cases. Using Sullivan 1-minimal models, Falk proves that also φ k (G A ) is combinatorially determined [Fal88]. He also obtains with Randell [FR85], in the particular case of fibertype arrangements, the LCS formula:…”
Section: Lower Central Series Quotientsmentioning
confidence: 89%
“…We will define in the latter sections a series of invariants of both H ≤2 (X) and G/G 3 , and relate them one to another. For now, let us define invariants of χ, following an idea of Ziegler [34], that originated from Falk's work on minimal models of arrangements [10].…”
Section: 16mentioning
confidence: 99%
“…The arrangement of hyperplanes is of fiber-type if there is a tower M = M n pn → M n−1 → · · · p 2 → M 1 = C * where each M k is the complement of an arrangement of hyperplanes in C k , and where p k is the restriction of a linear map C k → C k−1 whose fiber is a copy of C with finitely many points removed. In that case the minimal Sullivan model (∧V, d) of M satisfies V = V 1 ( [29]).…”
Section: The Complement Of Arrangementsmentioning
confidence: 99%